Portugal : Selected Issues. (IMF Staff Country Reports; Country Report, 2015)
This Selected Issues paper takes stock of structural reforms in Portugal from a firm-level perspective. Structural reforms were the main available policy tool to mend Portugal's accumulated imbalances. Portugal's macroeconomic toolbox was severely constrained by monetary union membership and spillover considerations. This paper discusses what structural reforms were supposed to achieve at the firm level. It documents a few stylized facts about Portuguese firms and describes the structural reform agenda. The paper also reports the results of a firm survey on the perceived effectiveness of the structural reforms.